Preferences in selection and planting types of roses (Rosa spp.) in urban public and semi-public areas: a case study of Bežigrad community, Ljubljana - Nina KUNC; Valentina SCHMITZER (Acta Agriculturae Slovenica, 2021)
Roses have an indisputable leading role in private gardens. They also appear in public areas. They are very interesting plants for public urban areas because they represent aesthetic, ecological, tehnical and sociological potential. In public areas varietes are selected according to various criteria such as resistance to heat, low temperatures an drought, repetitive flowering and ease of maintenance. The aim of our study is to present preferences in the selection of groups of roses, their colors, types of plantings, the abudance of roses in planting and the height of individual roses on difrent subtypes of public ans semi-public green areas of the Bežigrad community, Ljubljana. The results of the study showed that the most comomn roses in urban public areas are floribundas. Dominated type of planting is a few plants together in a group. In neighborhoods and block settlements are dominated individual plants. The most common color of roses is red. In urban public areas are planted only roses up to 1 m height. In semi-public areas are also higher roses. The abudance of roses in semi-urban areas varies from 1 to over 30 roses in planting. In urban public areas are most common planting with 10 to 20 roses and those with more than 30 roses.